Long-Term Neuroanatomical Consequences of Childhood Maltreatment: Reduced Amygdala Inhibition by Medial Prefrontal Cortex - Kessler, Roman; Schmitt, Simon; Sauder, Torsten; Stein, Frederike; Yüksel, Dilara; Grotegerd, Dominik; Dannlowski, Udo; Hahn, Tim; Dempfle, Astrid; Sommer, Jens; Steinsträter, Olaf; Nenadic, Igor; et al. (Frontiers in Systems Neuroscience, 2020)
Similar to patients with Major Depressive Disorder, healthy subjects at risk for depression show hyper activation of the amygdala as response to negative emotional expressions. Medial prefrontal cortex is responsible for amygdala control. Analyzing a large cohort of healthy subjects, we aimed to delineate malfunction in amygdala regulation by medial prefrontal cortex in subjects at increased risk for depression, i.e. with a family history of affective disorders or a personal history of childhood maltreatment. We included a total of 342 healthy subjects from the FOR2107 cohort (www.for2107.de). An emotional face matching task was used to identify medial prefrontal cortex and right amygdala. Dynamic Causal Modeling was conducted and neural coupling parameters were obtained for healthy controls with and without particular risk factors for depression. We assigned a genetic risk if subjects had a first-degree relative with an affective disorder and an environmental risk if subjects experienced childhood maltreatment. We then compared amygdala inhibition during emotion processing between groups. Amygdala inhibition by medial prefrontal cortex was present in subjects without those two risk factors, as indicated by negative model parameter estimates. Having a genetic risk (i.e. a family history) did not result in changes of amygdala inhibition compared to no risk subjects. In contrast, childhood maltreatment as environmental risk has led to a significant reduction of amygdala inhibition by medial prefrontal cortex. We propose a mechanistic explanation for the amygdala hyperactivity in subjects with particular risk for depression, in particular childhood maltreatment, caused by a malfunctioned amygdala down regulation via medial prefrontal cortex. As childhood maltreatment is a major environmental risk factor for depression, we emphasize the importance of this potential early biomarker.